Uma análise da atuação da auditoria operacional em empresas de transformação na cidade do Rio de Janeiro: um estudo de casos - Teixeira, Ivandi Silva (1989)
The purpose of this research was to analyse the works of internal auditing in its operational mode on industrial firms in the city of Rio de Janeiro, concerning the organizational structure and its functioning, and also considering its individual characteristics in conformity with the field or operated sector of each firm, related to the studied literature. The literature revised presented on chapter II, focalizes relevant aspects which were used as theoric bases to guide the present study. On chapter III the methodology used is presented, where we emphasize the case study methods, considering the lack of empirical verifications on internal auditing, as well as the choice for a thorough description about audit practices used by the firms here studied. Next, on chapter IV, the cases studied are described considering the characteristics of each audit department, and the means with which they develop their work. On chapter V, case analysis is presented in comparison with topics seen as important in literature. Finally, on chapter VI, we presented the conclusions, recommendations suggestions of new studies.